Perception and Reliance of Local Communities in Conservation of Protected Areas - Dhakal, Bhola Nath (Rupantaran: A Multidisciplinary Journal, 2023)
Conservation achievement is strongly inclined by perceptions of the impacts that are experienced by local communities. Perceptions provide an important means of assessing the performance of conservation plan so that better policies may be developed for effective biodiversity protection and the wellbeing of people living near protected areas. Local communities living adjacent to protected areas (PA) have played a vital role in biodiversity conservation. Understanding communities’ use and perceptions of a PA will increase its conservation effectiveness through reducing anthropogenic pressures and improving park-people relationship. The specific objective of the study was to explore the perceptions and reliance of local communities in conservation by different social groups and economic conditions on the basis of the current natural resource related needs in Bardia National Park (BNP) and its Buffer Zone (BZ). Data has been collected through a mixed-method approach, including qualitative semi-structured interviews and a household survey. This study confirmed that despite of the property loss and protected area management cost owed by local people, they are very much willing to contribute to biodiversity conservation, and in addition, their overall attitude towards various conservation statements is positive.